2017
DOI: 10.1016/j.jacc.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement in Pure Native Aortic Valve Regurgitation

Abstract: Compared with the early-generation devices, TAVR using the new-generation devices was associated with improved procedural outcomes in treating patients with pure native AR. In patients with pure native AR, significant post-procedural AR was independently associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
195
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(208 citation statements)
references
References 28 publications
8
195
1
4
Order By: Relevance
“…Since 2015, second‐generation valve systems were widely used, which could explain the better outcomes over the recent years besides improved patient selection and learning curves. A registry including over 300 patients with pure AR undergoing TAVR confirmed that treatment with second‐generation TAVR valves might achieve improved 1‐year outcomes . Therefore, convincing results with TAVR seem to be possible, assuming a thorough patient and TAVR‐valve selection in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Since 2015, second‐generation valve systems were widely used, which could explain the better outcomes over the recent years besides improved patient selection and learning curves. A registry including over 300 patients with pure AR undergoing TAVR confirmed that treatment with second‐generation TAVR valves might achieve improved 1‐year outcomes . Therefore, convincing results with TAVR seem to be possible, assuming a thorough patient and TAVR‐valve selection in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Compared to the early-generation devices, the new ones were associated with a significantly higher device success rate (81.1% vs. 61.3%, P < 0.001) due to lower rates of second valve implantation and post-procedural AR (more than moderate). The cumulative rates of all-cause and cardiovascular death at 1-year follow-up were similar and post-procedural AR was independently associated with worse outcomes [42] . Similar findings were showed by Franzone et al [43] that confirmed TAVI as technically feasible in AR patients, with acceptable early morbidity and mortality rates [43] .…”
Section: Patients With Pure Aortic Regurgitationmentioning
confidence: 79%
“…However, limited data exist about safety and efficacy of TAVI in this specific subset of patients, mainly reported in several case reports and small clinical studies. Yoon et al [42] enrolled 331 patients with symptomatic, severe pure native AR undergoing TAVI across 40 participating centers between September 2007 and February 2017. The aim of this study was to compare the outcomes of TAVI with early-and new-generation prosthesis devices in symptomatic patients with pure AR.…”
Section: Patients With Pure Aortic Regurgitationmentioning
confidence: 99%
“…Newer devices had higher device success rate (81% vs 61%; P < 0.001), and lower post‐procedural AR > moderate (4% vs 19%; P < 0.001). At 1 year, cardiovascular mortality was lower in patients who received newer devices (10% vs 24%, P = 0.008) …”
Section: Adjunctive Therapies and Imaging In Tavrmentioning
confidence: 99%